Two new species of Rhinogobius (Gobiiformes: Oxudercidae) from Palawan, Philippines, with their phylogenetic placement - Maeda, Ken; Shinzato, Chuya; Koyanagi, Ryo; Kunishima, Taiga; Kobayashi, Hirozumi; Satoh, Noriyuki; Palla, Herminie P. (Zootaxa, 2021)
Two new species of Rhinogobius found in streams on central part of Palawan Island, Philippines are described. The two new species, Rhinogobius estrellae and Rhinogobius tandikan share unique transverse rows of sensory papillae on the cheek with Rhinogobius similis Gill, 1859, but differ from the latter in fin ray counts, arrangement of the scales, etc. The two new species are distinguished from each other by the pectoral-fin ray count, the longitudinal- and predorsal-scale counts, and colouration of the body. Rhinogobius estrellae new species and R. tandikan new species have been found allopatrically in a stream within Malatgao River system flowing into the Sulu Sea and in the Cayulo River flowing into the South China Sea, respectively. The Malatgao River system is the southernmost habitat of the genus Rhinogobius. Rhinogobius similis had been considered as the only member of the most basal lineage of this genus, but our mitochondrial genome analysis suggested that the two new species are additional members of this lineage. They are considered to be relicts of their common ancestor with R. similis, which probably had a wider distribution.